PEMBUKTIAN DALAM PERKARA PERCERAIAN DENGAN ALASAN PERSELISIHAN - Adnyana, I Gusti Ngurah (Jurnal Cakrawala Hukum, 2013)
Civil Law was public law which was imperative so it tied everyone, especially in investigating witness incourt. It was determined that judge forbade to get witness from blood relative as the base to take decision.However it was not an absolute regulation. It meant that the rule of forbidding to investigate witness fromfamily side would not be in valid when a judge investigated witness in divorce case with continuous conflicts.Witness from family tended not too objective but a judge gave a priority on formal truth without testingmaterially. In fact in taking decision, a judge considered the regulation text more than the explanation fromwitness.